PENGARUH VOLUME PENYIRAMAN PUPUK CAIR URINE SAPI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI MERAH BESAR (Capsicum annum L) - Hans Maxson Elroy Parihala; J F Rehena (BIOPENDIX, 2016)
Background: Organic fertilizers is able to maintain the balance of the land and improve land productivity as well as reducing the environmental impact of land. Pepper plants contain lots of vitamin A and vitamin C and contain essential oils capsaicin, which causes a spicy flavor and heat to provide warmth when used for spices (herbs). Methods: The materials used in this study is the land of black, red chilli seeds large, EM4, water immersion soy, turmeric and wastewater cow urine. The study was conducted over three months, from April 2015 - July 2015. This study used a completely randomized design (CRD) with a liquid treatment factors limbar cow urine at levels as follows: P0 = control, ML P1 = 25, P2 = 50 ML and P3 = 75 ML. Each treatment was repeated 3 times. Data were analyzed using analysis of variance and if there is an influence, it will be followed by Least Significant Difference Test (BNT) at significance level of 5% and 1%. Results: The results showed that administration of cow urine liquid waste significant effect on the growth of large red pepper plant, that plant height, fruit number and weight of the fruit harvest. Conclusion: The growth of large red pepper plant with the highest scores were obtained in treatment P3 with a concentration of 75 ml while the growth to the lowest value was obtained in treatment P1 with a concentration of 25 ml